Handbook of National parks, wildlife sanctuaries and biosphere reserves in India - Negi, S.S. (New Delhi, 2012)
This book describes in brief the details of National Parks, Wildlife Sanctuaries and Biosphere Reserves in India. The description of flora (forest) types is after Champion & Seth (1968), and Negi (1989); fauna after Prater (1957); list of protected areas after WII (2008). Other information such as the best time to visit, accommodation, etc. has been collected from various sources. This revised edition incorporates all details till Dec. 2011.
Keywords: National parks-India